Considering the Psychological State of the Mukallaf in the Sharii Discourse: An Usuli and Maqasidi Study - Ahmed Muhammed Dakheel, (Islamic Sciences Journal, 2025)
This study explores the psychological dimension in Islamic legislation from an Usuli and Maqasidi perspective by examining scriptural evidences that consider the psychological state of the mukallaf (legally responsible person). It is grounded in the Usuli principle that Sharia is based on ease, the removal of hardship, and attention to people’s psychological and social conditions, as reflected in the Qur’anic affirmation that no hardship is placed in religion and in the Prophet’s instruction: “Make things easy and do not make them difficult.” The present paper argues that considering psychological states is not merely an ethical or educational value but constitutes one of the higher objectives (maqasid) of Sharia related to preserving life, intellect, honor, and social stability. This dimension appears clearly in the prohibition of marrying two sisters simultaneously, or a woman with her paternal or maternal aunt—rulings that demonstrate the Sharia’s sensitivity to emotional and psychological relationships among relatives. Such unions may lead to jealousy, conflict, and the severing of kinship ties, contradicting the Sharia’s aim of maintaining family harmony. Jurists unanimously upheld this prohibition based on explicit Qur’anic evidence, while Usuli scholars view it as an application of sadd al-dhara’i‘ (blocking the means) to prevent psychological and social harm.